Enhancing Islamic Education through Technology Integration: A Study of Teaching Practices in Indonesia - Siregar, Hariman Surya; Nurhamzah, Nurhamzah; Munir, M.; Fikri, Miftahul (Jurnal Ilmiah Peuradeun, 2025)
The integration of technology in education presents both opportunities and challenges, particularly in the context of Islamic education, where maintaining pedagogical effectiveness while embracing digital tools remains a key concern. This study aims to analyze technology integration in Islamic education, explore educators’ strategies to enhance student engagement and understanding, and identify challenges and opportunities related to technology use, including artificial intelligence and social media, to optimize digital-based learning. Employing a quantitative cross-sectional survey design, the study collected data from 11,372 Islamic education teachers across Indonesia, following a pilot phase involving 569 teachers. The findings indicate a generally positive reception of technology integration, with a high overall average response (4.4035), demonstrating its perceived effectiveness in supporting student engagement and comprehension. Key recommendations include enhancing teacher training programs, improving technological infrastructure, and adopting a balanced pedagogical approach to optimize educational outcomes.